ChatGPT integration in Chinese language pedagogy: a Vietnamese multi-institutional study - Phuoc Tai Nguyen; Hung Thanh Nguyen; Thuan Quy Nguyen (Institute of Advanced Engineering and Science, 2026)
This study investigates ChatGPT integration effectiveness in Chinese language education across three Vietnamese universities involving 350 students and 45 instructors. Using mixed-methods analysis, quantitative surveys revealed 78.3% improved learning motivation with artificial intelligence (AI)-enhanced personalized learning, while 82.1% valued immediate feedback capabilities. Significant disciplinary variations emerged: traditional medicine students demonstrated highest acceptance rates (M=4.3, SD=0.7) compared to translation studies students (M=3.7, SD=1.0), F(2, 347)=15.8, p<0.001. AI literacy was strongly associated with learning effectiveness (r=0.67, p<0.001), accounting for 45% of outcome variance. Qualitative analysis identified human-AI interactive negotiation competence (HAINC) development as critical, with 91% of instructors emphasizing systematic training needs. Despite benefits, 64.7% expressed human interaction concerns, revealing fundamental pedagogical tensions requiring collaborative human-AI frameworks. Findings provide evidence-based guidance for implementing discipline-responsive AI systems in Vietnamese higher education while maintaining pedagogical authenticity and addressing technological literacy gaps.